Peran Ulama dan Tokoh Masyarakat Sukabumi dalam Memperjuangkan dan Mempraktikan Kebijakan Publik di Negara Kesatuan Republik Indonesia - Munandi Saleh (Hadara : Journal of Da'wah and Islamic Civilization, 2026)
This article aims to conduct a historical-analytical examination of how religious scholars and community leaders in Sukabumi—particularly K.H. Ahmad Sanusi (1888–1950)—advocated for and applied principles of public policy in the context of resistance to colonialism, nation-building, and post-independence governance in the Republic of Indonesia. This study employs a qualitative approach with a historical-interpretive design. Data were collected through analysis of colonial archives (ANRI), BPUPKI documents, the written works of K.H. Ahmad Sanusi, in-depth interviews with the figure’s descendants and students, as well as primary and secondary academic literature. The analysis employs the frameworks of Historical Institutionalism, the Policy Paradigm, and the New Public Service. The study identifies three main dimensions of the Sukabumi ulama’s public policy practices: (1) transformative educational policies through pesantren as instruments for human resource empowerment and cultural resistance; (2) social policies grounded in maqashid al-syariah that prioritize the public interest (maslahah ‘ammah) over individual or group interests; and (3) inclusive political participation policies that reconciled Islamic values with the democratic principles of Pancasila during the 1945 BPUPKI sessions. Ulama and community leaders in Sukabumi have demonstrated that public policies rooted in religious values, local wisdom, and community participation constitute an authentic, legitimate, and sustainable governance model. This legacy offers an alternative paradigm for contemporary Indonesian public policy design, which is currently seeking its identity amid globalization and digital disruption.